MicroRNA analysis of porcine muscle tissue involved in phosphoinositol metabolism - Xie, Yuxiao; Cheng, Wenjie; Hao, Meilin; Yi, Lan-lan; Zhu, Jun-hong; Zhao, Yan-guang; Zhao, Sumei (Frontiers in Veterinary Science, 2025)
IntroductionTo elucidate the role of miRNAs in porcine muscle tissues, this study used Solexa high-throughput sequencing to identify and compare differentially expressed miRNAs in Landrace pigs and the Diannan small ear pigs.MethodsSmall RNA libraries were constructed from high-quality RNAs extracted from the Longissimus dorsi muscle (LDM) muscles of the two breeds of pigs and high-throughput sequencing was performed to identify and compare differentially expressed of miRNAs (DEmiRNAs). The target genes corresponding to the differentially expressed miRNAs were subjected to functional annotation, Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genomes (KEGG) pathway enrichment analysis.Results241 known conserved miRNAs sequences and 20 novel miRNAs in the Diannan small ear pigs library and known conserved miRNAs sequences and 22 novel miRNAs in the Landrace pigs library were identified. It is noteworthy that 14 miRNAs showed significant expression differences between the two pig breeds, and the expression levels of these miRNAs were lower in the Diannan small ear pigs than the Landrace pigs, among which the most significantly difference was miR-27a. GO and KEGG analyses showed that 26 target genes of DEmiRNAs were associated with inositol phosphate metabolism and phosphatidylinositol signalling pathways including INPPL1, INPP5J, INPP5A, INPP5B, INPP4A, INPP4B, INPP1, IMPAD1, DGKZ, CDLPT, CALM1, PLCG1, PLCCD3, PLCB4, PIP4K2A, PIK3R1 and PIK3CB, PIK3CA, ITPKC and ITPK1 genes which may be key genes regulating phosphatidylinositol 4,5-bisphosphate (PIP2), phospholipase C (PLC), inositol triphosphate (IP3), protein kinase C (PKC), calcium (Ca2+) and diacylglycerol (DAG).ConclusionThe findings of this study provide a theoretical framework for a more comprehensive understanding of the biological functions of miRNAs in muscle tissues, and lay a foundation for the discovery and utilisation of high-quality germplasm resources of the Diannan small ear pigs.